Transdifferentiation of polymorphonuclear neutrophils to dendritic-like cells at the site of inflammation in rheumatoid arthritis: evidence for activation by T cells. Issue 10 (18th March 2005) - Iking-Konert, C; Ostendorf, B; Sander, O; Jost, M; Wagner, C; Joosten, L; Schneider, M; Hänsch, G M
Abstract : Objectives: To investigate infiltrated cells in the synovial fluid (SF) of inflamed joints of patients with rheumatoid arthritis (RA), with special reference to polymorphonuclear neutrophils (PMN) and their interaction with T cells. Methods: Expression on PMN of activation associated receptors CD14, CD64, CD83, and major histocompatibility complex (MHC) class II was examined in the SF of 15 patients with RA, as were the infiltrated T cells. SF cytokines were determined by enzyme linked immunosorbent assay (ELISA). To mimic the in vivo situation, co-culture experiments were carried out using PMN and T cells of healthy donors. Results: The SF contained activated T lymphocytes and abundant PMN. SF PMN expression of CD14 and CD64 was enhanced compared with peripheral blood. Of special interest was the observation that only the SF PMN expressed MHC class II antigens and CD83. Exposure to SF, which contained considerable amounts of cytokines (for example, interferon γ (IFNγ), tumour necrosis factor α, and interleukin 2), induced a similar receptor pattern on blood derived PMN of healthy donors. Furthermore, PMN acquired MHC class II and CD83 within 24 to 48 hours, when co-cultured with autologous T cells or T cell lines. This effect was also achieved by T cell supernatants, was dependent on protein synthesis, and could be inhibited by antibodies against IFNγ. Conclusions: SF PMN from patients with RA undergo major alterations, including transdifferentiation to cells with dendritic-like characteristics, probably induced by T cell derived cytokines. Because MHC class II positive PMN are known to activate T cells, the mutual activation of PMN and T cells might contribute to the perpetuation of the local inflammatory process, and eventually to the destructive process in RA.